Development of coupled centrifuge-numerical modelling: investigation of global tunnel-building interaction - Franza, Andrea; Marshall, Alec M.; Abdelatif, Amged O.; Cox, Craig M. (2014)
There is an increasing demand for underground space in urban areas for infrastructure development. This has resulted in tunnel construction taking place in close proximity to buried infrastructure and building foundations. Various studies have considered the effect of tunnel construction on buildings; however the global tunnel-ground building interaction problem is still not well understood. This is due partially to the fact that the available modelling tools do not accurately replicate the global behaviour of soil-structure domains. This research aims to enhance physical modelling capabilities by coupling centrifuge and numerical techniques. The research focuses on tunnelling beneath buildings which are founded on piled foundations. In this paper, the proposed method and the developed equipment are presented. The expected outcomes of this research will provide a better understanding of complex tunnel-ground-building interactions which will help to improve the design approach of tunnels beneath buildings.